Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) terhadap Hasil Belajar Simetri di Sekolah Dasar - Atrinisia, Novi; Zainil, Melva; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective  of this study is to find out the effect of implementing the Pendidikan Matematika Realistik Indonesia (PMRI) approach on the learning results of symmetry in elementary school students. The type of research of this study is a quasi-experimental research with the research design of nonequivalent control group design. The research sample is the students of 5th-grade of class VA and class VB in state-owned elementary school No. 23 Marapalam, Padang. The sampling technique of this study is a purposive sampling. The study utilized a test in the form of multiple choise questions as the research instrument. Data were analyzed using the t-test. Based on the tcalculation(3,00) > ttable(2,00), it is concluded that there is a significant effect of the implementation of the Pendidikan Matematika Realistik Indonesia (PMRI) approach to the learning results of symmetry in elementary school.  Keywords: PMRI approach, learning results.